Dental conferences: Are they good for education? - Gupta, Dr. Suruchi; Thosar, Dr. Nilima; Baliga, Dr. Sudhindra; Rathi, Dr. Nilesh; Fulzele, Dr. Punit (IJRDO- Journal of Educational Research, 2017)
The current status of dental education in India has some pivotal challenges. There is a vital need to concentrate beyond the humdrum classroom learning and curriculum which can be partly addressed by sharing ideas with experts and community. There is a need to refine and reconstruct the current education pattern to create pioneers in the field of dentistry for meeting the expanding demands. Dental students in India are trained to excel theoretically, but there seems to be a vacuum between the theoretical and its clinical implications. Dental conferences endow with a variety of approaches and strategies related to management and quality improvement of dental clinic as well as explore new ideas and concepts. The aim of this article is to discuss the benefits associated with attending conferences as well as highlighting the scope for improvement of conduction of such conferences.